Global mining schools-poised for strategic growth - Hall, Stephen (Australian Centre for Geomechanics, 2011)
Risk reduction in the mining industry can be achieved through enabling quality people to do a quality job; through the actions of such people we can sustain the global industry and secure the social license to operate. However, there is global concern over where the numbers of such people are going to come from. Many mining schools in the developed world have closed and some of those that remain are being challenged by the auditing of research output (both quality and quantity). Industry and governments worldwide are becoming increasingly aware of the looming crisis and are putting in place significant initiatives to help address the problem. These include increased financial support, improved regional provision (including the development of new mining schools), and projects to recruit from under-represented sectors of the population (e.g. indigenous, women). This paper will offer a global overview of mining education and of some of these emerging initiatives.